Pengaruh Jumlah Penduduk, PDRB dan Pajak Daerah Terhadap Pendapatan Asli Daerah (PAD) Jawa Timur - Binti Munawaroh Fadil; Ajeng Wahyuni; Agyl Henggar Pradana (Niqosiya: Journal of Economics and Business Research, 2025)
Local Original Income (PAD) in one of the main indicators in assessing the independence and fiscal capacity of a region. This independence can be defined as the extent to which a region is able to finance the implementation of activities and development independently. The main objective of this study is to examine the Effect of Population, PDRB and Regional Taxes on Lokal Original Income (PAD) of East Java. This study uses a quantitative approach with an associative quantitative method with a five-year period, namely 2016-2020. The findings in this study are that individually or partially the population and regional tax variables have a significant effect on regional original income. For the PDRB variable, it partially has no effect on regional original income. While simultaneously the variables of Population, PDRB and Regional Tax have a significant effect on the Original Regional Income of East Java. With that, the government needs to plan developments policies that consider demographic factors so that population growth can be in line with the increase in the regional economy.